Activating students’ specialized knowledge through illustrations for marine engineering vocabulary learning at Maritime College No.1 - Đặng, Thị Hoàng Yến (University of Languages and International Studies, 2017)
With the open-door policy as well as the development trend in sea-transport economy, maritime English has become more and more multi-lingual and multi-cultural, thus mastering maritime English draws a public concern.